Emergency surgery for acute vein thrombosis - Palma, E; Bercianos, C.; del Campo, F; Schiaffarino, O.; Goller, W; Perillo, W; Fernández, E (Cirugía del Uruguay, 2020)
Presented at session 23rd May 1962